Mental Health Description and Predisposing Factors in Adolescent Females in Mekarbakti Village, Pamulihan District - Dyah Ayu Fitriani; Siti Rukmana (Green Health International Journal of Health Sciences Nursing and Nutrition, 2026)
Adolescents are at greater risk of mental health conditions. Good or bad mental health conditions in adolescents cannot be separated from the factors that influence it. Factors that influence adolescent mental health include religiosity, smartphone addiction, parenting patterns and peer interaction. The aim of this research is to determine the mental health picture and predisposing factors in young women in Mekarbakti Village, Pamulihan District, Sumedang Regency. The type of research is descriptive, the population is 508 young women in Mekarbakti Village, Pamulihan District, Sumedang Regency. The sample was taken using stratified random sampling so that 84 people were obtained. Data collection is done by filling out a questionnaire. Data analysis uses univariate analysis in the form of frequency distribution. The research results showed that more than half had good mental health, 52 people (61.9%), more than half had high religiosity, 49 people (58.3%). more than half of them are not addicted to smartphones as many as 48 people (57.1%), more than half have democratic parenting as many as 59 people (70.2%), more than half of them have high peer interaction as many as 48 people (57.1%). The conclusion was that more than half of young women's mental health was good, their religiosity was high, they were not addicted to smartphones, their parenting was democratic and their peer interaction was high. Suggestions for research sites could be to hold positive activities for young women, such as by encouraging more young people to take part in Karang Taruna activities